Bielza de Ory, V. (2022) Lo urbano y lo sagrado. Morfología de la ciudad occidental. : Reseña bibliográfica - Callizo-Soneiro, Javier (Geographicalia, 2022)
Contrary to the current inaugurated by V. Gordon Childe for whom the city would be a consequence of the previous invention of agriculture, Bielza de Ory seems to lean openly towards the thesis of Fustel de Coulanges, for whom the altar would be "the first element of the urban cradle”. This thesis is supported by recent archaeological discoveries (Jericho; Caral and Çatal Hüyük,) whose dating would be prior to the Agricultural Revolution. In the historical journey that the author offers us, the sacred has played a role that is not relevant but expressly decisive in the genesis of the urban form in the West. And it has not ceased to have it despite the process of secularization that the industrial era is undergoing and that instead would have changed in the postmodern era, in which the sacred, fast from all transcendence, would have been revalued even as an outstanding part of the cultural heritage